2015
DOI: 10.1002/lt.24103
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor as a potential predictor for requirement of renal replacement therapy after orthotopic liver transplantation

Abstract: Acute kidney injury (AKI) after orthotopic liver transplantation (OLT) is associated with a poor clinical outcome. Because there is no specific treatment for postoperative AKI, early recognition and prevention are fundamental therapeutic approaches. Concentrations of the proinflammatory cytokine macrophage migration inhibitory factor (MIF) are elevated in patients with kidney disease. We hypothesized that plasma MIF concentrations would be greater in patients developing AKI after OLT compared with patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…We recently demonstrated that systemic MIF concentrations increase after reperfusion in patients undergoing OLT . In agreement with our previous findings, MIF concentrations increased in the serum of patients undergoing OLT after reperfusion in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We recently demonstrated that systemic MIF concentrations increase after reperfusion in patients undergoing OLT . In agreement with our previous findings, MIF concentrations increased in the serum of patients undergoing OLT after reperfusion in this study.…”
Section: Discussionsupporting
confidence: 93%
“…demonstrated a close relation between concentrations of MIF in serum with markers of cellular damage such as ALT, AST, and LDH in patients after cardiac arrest . Recently, we found that elevated MIF concentrations after OLT were associated with postoperative acute kidney injury . In the current study, we report an association between MIF and postoperative liver graft function.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, postoperative kidney function was assessed according to the KDIGO criteria, 20 and patients were assigned to the 'no/mild AKI' (no AKI and stage 1 AKI) and 'severe AKI' (stage 2 and 3 AKI) group, as previously described. 21,22 Sample collection and analysis Blood samples were collected from an arterial line at following time points: at baseline after induction of anesthesia, at the end of OLT (End OLT), and on the morning of the first, second, and third postoperative day (POD1, POD2, and POD3, respectively). Immediately after collection, serum samples were allowed to set for 30 min, centrifuged at 2600 g for 15 min, and stored at −80 C until analysis.…”
Section: Patients and Perioperative Datamentioning
confidence: 99%
“…Some studies have shown an association between pre‐operative serum creatinine and concordant MELD score with post‐liver transplantation AKI, whereas others have not . Furthermore, as serum creatinine has been shown to overestimate the glomerular filtration rate in cirrhotic patients, it is an inaccurate marker for renal function in this patient population . Thus, we deliberately decided not to include pre‐operative serum creatinine as an individual parameter in this analysis.…”
mentioning
confidence: 99%